Perlindungan Hukum Terhadap Kekerasan pada Anak - Rianawati Rianawati (Raheema, 2015)
There are many types and causes in a violence behavior. One of the action in the domestic field is the violence performed by parents, family, and the close neighborhood on children. Furthermore, the children abuse violates the human rights since as a humankind, children have the rights even from their birthday. The children assault will dangerously cause the fatal result, physically and psychologically on a child. The violences on children are the act against the laws, UN Declaration about Human Rights and UU RI No. 39 Tahun 1999 verse 53. Besides, Islam prohibits the violent acts on children as well.